2016
DOI: 10.1016/j.echo.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Two-Dimensional Interrogation of the Tricuspid Valve Using Knowledge Derived from Three-Dimensional Echocardiography

Abstract: Background Accurate identification of tricuspid valve (TV) leaflets by two-dimensional (2D) transthoracic echocardiography is difficult because of variability in the intersection between the imaging plane and leaflets. Using information obtained from multiplanar reconstruction (MPR) of three-dimensional (3D) data sets, the investigators sought to define “novel” 2D views that would allow targeted interrogation of TV leaflets using 2D transthoracic echocardiography. Methods Images of the TV in the standard 2D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“… The best TR signal is often “off-axis,” in-between parasternal and apical windows. An RV-focussed or fore shortened 4-chamber view might give the best signal [12] . Sometimes, subcostal long and short axis windows provide the optimal signal and incident angle.…”
Section: Pulmonary Artery Systolic Pressure By Tr Peak Velocitymentioning
confidence: 99%
“… The best TR signal is often “off-axis,” in-between parasternal and apical windows. An RV-focussed or fore shortened 4-chamber view might give the best signal [12] . Sometimes, subcostal long and short axis windows provide the optimal signal and incident angle.…”
Section: Pulmonary Artery Systolic Pressure By Tr Peak Velocitymentioning
confidence: 99%
“…Since then, transducers, software and hardware have improved dramatically in terms of acquisition, temporal and spatial resolution and image rendering. Several studies have confirmed the superiority of 3DTTE in the evaluation of the MV apparatus as well as of the aortic (AV) and tricuspid valve (TV) [ 6 , 7 , 8 , 9 ].…”
Section: Assessment Of Valve Pathologiesmentioning
confidence: 99%
“…Indeed, the RCA is at risk for injury during the procedure, especially if located in close proximity to the site of implantation. An "en face" view of the TV is typically obtained on an LAO fluoroscopic projection and allows for antero-posterior orientation alongside the RCA (Figures 5B,D) and corresponds to the TEE transgastric short axis view (103,104). In this view, the ostium and proximal part of the RCA surrounds the anterior valve leaflet while the periphery is close to the posterior leaflet.…”
Section: Transcatheter Annuloplastymentioning
confidence: 99%